Job Stress and Work Environment as Determinants of Employee Performance in the Indonesian Private Sector - Muhammad Arif Lubis; Ilham Sentosa; Gerhard Wilhelm Weber (TALENTA Publisher, Universitas Sumatera Utara, 2025)
Employee performance is a critical factor in achieving organizational goals andsustaining competitive advantage. This study investigates the influence of jobstress and work environment on employee performance at PT. Rahayu Permai.Employing a quantitative research design, data were collected through structuredquestionnaires distributed to employees and analyzed using multiple linearregression techniques. The results indicate that job stress has a negative andsignificant effect on employee performance, while the work environment exertsa positive and significant influence. These findings highlight the importance oforganizational efforts to minimize work-related stress and improve workplaceconditions in order to enhance employee productivity and overall performance